Analysis of Visual Scanning Patterns Comparing Drivers of Simulated L2 and L0 Systems. Issue 10 (October 2019) - Hatfield, Nathan; Yamani, Yusuke; Palmer, Dakota B.; Yahoodik, Sarah; Vasquez, Veronica; Horrey, William J.; Samuel, Siby
Automated driving systems (ADS) partially or fully perform driving functions. Yet, the effects of ADS on drivers' visual sampling patterns to the forward roadway remain underexplored. This study examined the eye movements of 24 young drivers during either manual (L0) or partially automated driving (L2) in a driving simulator. After completing a hazard anticipation training program, Road Awareness and Perception Training, drivers in both groups navigated a single simulated drive consisting of four environment types: highway, town, rural, and residential. Drivers of the simulated L2 system were instructed to keep their hands on the steering wheel and told that the system controls the speed and lateral positioning of the vehicle while avoiding potential threats on the forward roadway. The data indicate that the drivers produced fewer fixations during automated driving compared with manual driving. However, the breadth of horizontal and vertical eye movements and the mean fixation durations did not strongly support the null results between the two conditions. Existing hazard anticipation training programs may effectively protect drivers of partially automated systems from inattention to the forward roadway.